Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/02688697.2015.1019418
|View full text |Cite
|
Sign up to set email alerts
|

Neuronavigation-assisted percutaneous balloon compression for the treatment of trigeminal neuralgia: The technique and short-term clinical results

Abstract: We believe that image-guided neuronavigation is useful for neurosurgeons who are at the beginning of their PBC learning curve. It may also be an alternative for particular patients with significant anatomic variations that result in an unsuccessful foramen ovale puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…89 Although fluoroscopy has been the imaging modality of choice, newer studies have demonstrated the potential usefulness of computed tomography, Dynacomputed tomography, and neuronavigation systems, especially for patients with anatomic variants that may prevent successful access with traditional means. [90][91][92][93] In 1 study of RFT, guidance with computed tomography fluoroscopy allowed for successful engagement of the foramen ovale on the first attempt, all requiring less than 40 seconds. 94 The use of neuronavigation for PBC in a series of 174 patients resulted in complete pain relief in all patients, and no complications.…”
Section: Discussionmentioning
confidence: 99%
“…89 Although fluoroscopy has been the imaging modality of choice, newer studies have demonstrated the potential usefulness of computed tomography, Dynacomputed tomography, and neuronavigation systems, especially for patients with anatomic variants that may prevent successful access with traditional means. [90][91][92][93] In 1 study of RFT, guidance with computed tomography fluoroscopy allowed for successful engagement of the foramen ovale on the first attempt, all requiring less than 40 seconds. 94 The use of neuronavigation for PBC in a series of 174 patients resulted in complete pain relief in all patients, and no complications.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional rotational fluoroscopy has been described as an option [13] but it requires specific training that is not part of the routine of specialists in functional neurosurgery. Intraoperative mobile CT coupled or not to a neuronavigation system is another option with good results [14], but this technology is not available at many neurosurgery services in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronavigation is a widely adopted technology in modern neurosurgery [ 3 , 4 , 6 , 9 , 11 , 17 , 18 , 27 , 28 , 35 , 36 ]. The trajectory for RF-TR is chosen along an unobstructed linear pathway through the foramen ovale, and the placement of needle tip usually does not exceed the clival line confirmed by fluoroscopy [ 4 , 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%